Death and Ubuntu in Oliver Mtukudzi's Music. Issue 1 (2nd January 2020) - Chasi, Colin; Tagwirei, Cuthbeth
Abstract: The musical lyrics of the late Oliver "Tuku" Mtukudzi (1952–2019), by focusing on social-cultural values and practices, are an unexplored but valuable resource for the purpose of thinking about ubuntu and death. In this article, the authors put forward a nuanced examination of the corpus of Tuku's music on death that reveals multiple, inconsistent, contradictory and interrelated insights into how ubuntu and death speak to each other. Getting to deep understandings of some of these consistencies and contradictions requires examination of the contexts, audiences, motives, and other factors that relate to particular songs. In part because of this the authors do not seek to suggest that any contradictions or inconsistencies they identify are evidence of failures or omissions in Tuku's thoughts on ubuntu and death. Rather, they seek to recognise Tuku's appreciation for how ubuntu and death bear many contingent, commensurable, incommensurable, fragile and even unspeakable meanings in the existential course of a life – in the fearsome face of death. From this vantage point, the authors recognise and value Tuku's practices of (indirect) communication. Specifically, they aver that Tuku's indirect communication exemplifies right ways of talking about concerns relating to how people should live and die. In doing this, they offer new insights into right ways of conducting indirect communication to respectfully communicate, to produce and to reproduce desired societies in which everyone can be the most that they can be.